2008
DOI: 10.1111/j.1558-5646.2008.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Evolution and Stability of the G-Matrix

Abstract: The G-matrix summarizes the inheritance of multiple, phenotypic traits. The stability and evolution of this matrix are important issues because they affect our ability to predict how the phenotypic traits evolve by selection and drift. Despite the centrality of these issues, comparative, experimental, and analytical approaches to understanding the stability and evolution of the G-matrix have met with limited success. Nevertheless, empirical studies often find that certain structural features of the matrix are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
538
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(586 citation statements)
references
References 90 publications
20
538
1
8
Order By: Relevance
“…Within a theoretical context, developmental constraints must align with genetic constraints to have a lasting evolutionary impact [64]. Although certainly possible in theory, Anolis is a very old genus (estimated age is at least 40 million years [30]); finding conserved genetic architectures over such great periods of time might be considered surprising ( [65][66][67][68] and references therein; but see [69] for evidence of conserved phenotypic integration over long evolutionary timescales in anoles).…”
Section: Discussionmentioning
confidence: 99%
“…Within a theoretical context, developmental constraints must align with genetic constraints to have a lasting evolutionary impact [64]. Although certainly possible in theory, Anolis is a very old genus (estimated age is at least 40 million years [30]); finding conserved genetic architectures over such great periods of time might be considered surprising ( [65][66][67][68] and references therein; but see [69] for evidence of conserved phenotypic integration over long evolutionary timescales in anoles).…”
Section: Discussionmentioning
confidence: 99%
“…Although G-matrices are highly conserved among some populations (see Arnold et al (2008)), they have also been demonstrated to rapidly diverge among both natural populations and experimental treatments (Cano et al, 2004;Doroszuk et al, 2008;Hine et al, 2009;Johansson et al, 2012). Laboratory manipulations have demonstrated that G can evolve rapidly in response to drift (Phillips et al, 2001), and that selection can drive rapid and repeatable evolution of G (Blows and Higgie, 2003;Hine et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous empirical studies have taken a comparative approach to determine evolutionary rates, and the processes affecting G (Steppan et al, 2002;Arnold et al, 2008). Although G-matrices are highly conserved among some populations (see Arnold et al (2008)), they have also been demonstrated to rapidly diverge among both natural populations and experimental treatments (Cano et al, 2004;Doroszuk et al, 2008;Hine et al, 2009;Johansson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, general answers from simulations seem unlikely to emerge because it is extremely complex to consider all of the relevant parameters involved across the whole range of relevant parameter values (e.g. population size, number of loci, number of alleles, distribution of allelic effects, dominance, epistasis, mutation rate, strength of selection [11]). Therefore, if and how selection influences G remains largely an empirical question [11][12][13].…”
Section: Introductionmentioning
confidence: 99%